Reactive Oxygen Species and Gibberellin Acid Mutual Induction to Regulate Tobacco Seed Germination - Li, Zhan; Gao, Yue; Zhang, Yuchan; Lin, Cheng; Gong, Dongting; Guan, Yajing; Hu, Jin (Frontiers in Plant Science, 2018)
Seed germination is a complex process controlled by many mechanisms. To examine the potential contribution of reactive oxygen species (ROS) and gibberellin acid (GA) in regulating seed germination, diphenylene iodonium chloride (DPI) and uniconazole (Uni), as hydrogen peroxide (H2O2) and GA synthesis inhibitor respectively, were exogenous applied on tobacco seeds by seed priming. Seed priming with DPI or Uni decreased germination percentages as compared with priming with H2O, especially DPI+Uni combination. H2O2 and GA completely reversed the inhibition induced by DPI or Uni. The germination percentage of H2O2+Uni and GA+DPI combination kept the same level as H2O. Meanwhile, GA or H2O2 increased GA content and deceased ABA content through corresponding genes expression involving in homeostasis and signal transduction. In addition, the activation of storage reserves mobilization, enhancement of soluble sugar content and isocitrate lyase (ICL) activity, was also induced by GA or H2O2. These results strongly suggested that H2O2 and GA were essential for tobacco seed germination and there was a mutual induction between them to regulating seed germination. Meanwhile ICL activity was jointly mediated by ABA/GA balance and ROS concentration.